Historical research in organizational studies: Methodological itineraries in the light of Michel de Certeau - Lacerda, Carlos César de Oliveira; Ipiranga, Ana Silvia Rocha (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Recent years have witnessed a growing call for studies that articulate the approach to history in the context of organizational studies. These proposals illuminated the potential of historical research by presenting different methodological contributions to understanding organizational phenomena, highlighting the experience of people, society and organizations. Purpose: Considering the approach to history in organizational studies, this work proposes to present some methodological itineraries according to Michel de Certeau present in the works “The Writing of History” (Certeau, 2011) and “The Practice of Everyday Life:1- Fine Art of Dwelling" (Certeau, 2012). Method: A theoretical discussion was held. Initially, we present an overview of studies, focusing on questions specifically about methods of historical research in administration and organizational studies. Then, some ideas proposed in the work “The Writing of History” (Certeau, 2011) were presented, which were based on concepts about “The Productions of Place” that deal with methodological itineraries related to “Making History” and “The Historiographical Operation”. Furthermore, the concept of “Practices of Space.” proposed in the work “The Practice of Everyday Life:1- Fine Art of Dwelling" (Certeau, 2012) was considered, which outline the methodological itineraries related to “Walking in the City” and “Reports of Space”. Results: As a result, methodological contributions to researchers are emphasized with regard to the development of documentary research that reflects the “lessons of history” based on “units of understanding” in a mesh of spatio-temporal practices in the design of the research. Conclusions: Finally, some opportunities are highlighted to expand the possibilities of historiographical research in organizational studies considering the use of the approach of Michel de Certeau, according to a temporal historical logic of the organization of spaces reported by the memories of city walkers.